2012
DOI: 10.1038/jp.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of umbilical artery catheter-related thrombosis—a cohort study

Abstract: Objective: To reveal the incidence of umbilical artery catheter-related thrombosis (UACRT), the associated risk factors and the natural history of clot formation and regression.Study Design: A prospective cohort study. An umbilical artery catheter was inserted in 61 infants, who were evaluated and followed by serial duplex ultrasound studies for the development of UACRT, renal artery resistance index (RI) and clot resolution. Maternal and infant clinical variables were correlated with the characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
0
21
0
3
Order By: Relevance
“…Therefore, it is worrisome that in our attempt to demonstrate improved outcomes from umbilical vessel catheterization, we found that death was independently associated with UVC placementeven after adjusting for confounding variables such as birth weight, gestational age, and secondary morbid outcomes. Some investigators have questioned the advisability of UAC placement because of demonstrated thrombi in the aorta at autopsy or risks of bowel ischemia during enteral nutrition [5][6][7], but less has been published about the risks of UVC placement.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is worrisome that in our attempt to demonstrate improved outcomes from umbilical vessel catheterization, we found that death was independently associated with UVC placementeven after adjusting for confounding variables such as birth weight, gestational age, and secondary morbid outcomes. Some investigators have questioned the advisability of UAC placement because of demonstrated thrombi in the aorta at autopsy or risks of bowel ischemia during enteral nutrition [5][6][7], but less has been published about the risks of UVC placement.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective and prospective data are mostly from catheter-related RAT, and the reported incidence varies according to the method used to diagnose the event. The reported incidence based on clinical signs ranges from 1 to 3 %, that based on ultrasound (US)-based studies varies from 14 to 35 % and the highest incidence of RAT has been reported in ion angiographic investigations at 64 % [11,12]. With the increased use of central catheters for invasive therapeutic interventions, especially umbilical venous and umbilical artery catheters (UACs), as well as femoral catheters, the incidence of renal vascular thrombosis is expected to be much higher.…”
Section: Epidemiology Of Renal Vascular Thrombosismentioning
confidence: 99%
“…On the other hand, diagnosis of spontaneous RAT in the newborn is often suspected based on the presence of risk factors, as many infants only present with transient hypertension [12,18]. Acute renal insufficiency is rare, unless there is extension of thrombus in the aorta to occlude both renal arteries.…”
Section: Epidemiology Of Renal Vascular Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Umbilical artery CRT (UACRT) is usually asymptomatic and related to the duration of the catheter placement. 19 Shortterm complications include lower extremity ischemia, congestive heart failure, impaired renal function, and hypertension. Necrotizing enterocolitis has been reported as an embolic complication.…”
Section: Thrombotic Disorders In Neonatesmentioning
confidence: 99%